Re-Examining the Long-Term Effects of Experiencing Parental Death in Childhood on Adult Psychopathology. - Jacobs, John R. (2006)
Keywords: dept.psy; faculty_collection

Re-examining the long-term effects of experiencing parental death in childhood on adult psychopathology. - Jacobs, John R; Bovasso, Gregory B (Journal of Nervous and Mental Disease, 2009)
This study examined whether the experience of the death of a parent in childhood increases risk for adult psychopathology. Participants consisted of 3481 men and women gathered through the Baltimore Epidemiologic Catchment Area study in 1981 and followed through 1994-1995. The Diagnostic Interview Survey was administered by trained interviewers and was used to assess DSM-III disorders including major depression, panic, and anxiety disorders. Maternal death was not a predictor of adult psychopathology. The death of the father during childhood more than doubled the risk for major depressive disorder in adulthood. This study did not find any significant interactions between gender of the deceased parent and gender of the participant nor did the current age of the participant or their age at the time of the death of a parent affect risk for adult psychopathology. The long-term effect on adult depression of the experience of the death of the father in childhood is attributed to likely financial stresses, which may have continued for years and possibly into early adulthood, complicating the family's adaptation to the initial loss.
34 citations (Crossref) [2023-10-31] Place: United States Jacobs, John R. Department of Psychology, Southern Connecticut State University, New Haven, Connecticut, USA. jacobsj1@southernct.edu
Keywords: *Bereavement; *Death; *Mental Disorders/et [Etiology]; *Mental Disorders/px [Psychology]; *Parents; *Psychology; Child; Anxiety Disorders; Anxiety Disorders/di [Diagnosis]; Anxiety Disorders/et [Etiology]; Anxiety Disorders/px [Psychology]; Bereavement; Child Psychology; Death; Depression; Depressive Disorder; Major; Depressive Disorder; Major/di [Diagnosis]; Depressive Disorder; Major/ep [Epidemiology]; Depressive Disorder; Major/et [Etiology]; Depressive Disorder; Major/px [Psychology]; Diagnostic and Statistical Manual of Mental Disorders; Economics; Fathers; Female; Humans; Incidence; Male; Mental Disorders; Middle Aged; Mothers; Panic; Parental death; Parents; Prevalence; Risk Factors; Stress; Psychological; Stress; Psychological/et [Etiology]; Time Factors; adaptive behavior; adult; adulthood; anxiety disorder; article; bereavement; child psychology; childhood; death; depression; dept.psy; diagnostic and statistical manual of mental disorders; economics; family stress; father; female; gender; human; incidence; interview; major depression; male; maternal mortality; mental disease; mental stress; middle aged; mother; normal human; panic; parent; parental deprivation; personal experience; prevalence; psychological aspect; risk factor; time; time of death

Early and chronic stress and their relation to breast cancer - Jacobs, John R; Bovasso, Gregory B (Psychological Medicine, 2000)
Background. The study examined the role of parental death and chronic depression with severe episodes in affecting risk of breast cancer. This avenue of research is in accord with oncology findings, which suggests that causative factors of breast cancer occur and develop over a period of 20 years or longer. Methods. Participants consisted of 1213 women in the Baltimore Epidemiologic Catchment Area study surveyed in 1980 and followed through 1994-1995. They were assessed for depressive and anxious disorders, paternal death in childhood and relatively recent adverse life events prior to cancer hospitalization. Results. In the course of the study, 29 women were hospitalized for breast cancer and 10 died of breast cancer. The psychosocial variables that predicted increased risk of breast cancer were maternal death in childhood (OR = 2.56, P ¡ 0.001) and chronic depression with severe episodes (OR = 14.0, P ¡ 0.001). Neither relatively recent life events nor other depressive and anxiety disorders were associated with increased risk. Maternal death and chronic depression with severe episodes were reported to have occurred at least 20 years prior to breast cancer hospitalization. Conclusions. Maternal death and chronic and severe depression occurred at least 20 years prior to breast cancer hospitalization and could have been involved in the causation or facilitation of cancer development. The authors suggest that meta-analysis of other prospective studies are needed to create larger groups of individuals with these stresses to confidently establish these variables as risk factors.
83 citations (Crossref) [2023-10-31] Place: England Jacobs, J R. Department of Psychology, Southern Connecticut State University, New Haven 06515, USA. Comment in (CIN)
Keywords: *Breast Neoplasms/et [Etiology]; *Death; *Depressive Disorder/co [Complications]; *Stress; Psychological; Adult; Breast Neoplasms; Breast Neoplasms/px [Psychology]; Death; Depressive Disorder; Epidemiologic Studies; Female; Humans; Life Change Events; Middle Aged; Mother-Child Relations; Risk Factors; Stress; Psychological; adult; anxiety neurosis; article; breast cancer; cancer risk; depression; dept.psy; female; health survey; hospitalization; human; life event; major clinical study; medical psychology; mental stress; parental deprivation